Curcumin Regulates Anti-Inflammatory Responses by JAK/STAT/SOCS Signaling Pathway in BV-2 Microglial Cells - Chiara Porro; Antonia Cianciulli; Teresa Trotta; Dario Domenico Lofrumento; Maria Antonietta Panaro (Biology, 2019)
Microglia play important physiological roles in central nervous system (CNS) homeostasis and in the pathogenesis of inflammatory brain diseases. Inflammation stimulates microglia to secrete cytokines and chemokines that guide immune cells to sites of injury/inflammation. Neuroinflammation is also strongly implicated in the pathogenesis of a number of neurodegenerative diseases, including Alzheimer’s disease and Parkinson’s disease, for which nutritional intervention could represent a benefit due to a lack of clinically efficacious drugs. To this end, the anti-inflammatory mechanisms of several phytochemicals, including curcumin, have been extensively studied. The present experiments show that the administration of curcumin is able to increase the production of the anti-inflammatory cytokines, IL-4 and IL-10, in murine BV-2 microglial cells treated with lipopolysaccharide (LPS). Consistent with these data, curcumin stimulation upregulates the expression of Suppressors of cytokine signaling (SOCS)-1, whereas phosphorylation of the JAK2 and STAT3 was reduced. Taken together, these results provide evidence that curcumin is able to regulate neuroinflammatory reactions by eliciting anti-inflammatory responses in microglia through JAK/STAT/SOCS signaling pathway modulation.